PROTOTYPE ALAT PENDETEKSI KEKERUHAN DAN KEASAMAN AIR SUMUR DENGAN SENSOR LDR DAN SENSOR PH BERBASIS ARDUINO UNO DI DESA BUKIT TINGGI KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Roslan; samsuriadi; Raden Wirawan; muhammad awal nur (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2021)
This study aims (1) to make a tool that knows the level of turbidity and acidity of the water using an LDR sensor and a pH sensor. (2) To connect between LDR, PH and Arduino. (3) To read the turbidity and acidity of the water using an LDR sensor and an arduino uno-based pH sensor. The research method used is SDLC (System Development Life Cycle) model with the prototype method, while the steps in the prototype are gathering needs, rapid design processes ,building prototypes and evaluations, improvements, data collection techniques, observations, interviews and literature studies. The results of this study indicate that (1) The design of a prototype for detecting turbidity and acidity of well water uses an LDR sensor which can determine the cloudiness or clarity of water and uses a pH sensor to determine the acidity and alkaline levels of the water. (2) The implementation of this arduino-based prototype turbidity and acidity detector can be used by people who do not know the pH level of the water which is good for use.